Potential labour supply in the regions of the Nordic countries: A method to forecast and test regional patterns of potential labour supply - Torben Dall Schmidt; Aki Kangasharju; Daniel Rauhut (European Regional Science Association (ERSA), 2010)
Ageing is a central issue in policy debates in many countries. Much of the attention in the current debate is focused on (a) the labour supply and (b) aggregate problems at national levels. The present paper asks a distinct but related question by examining how ageing changes the regional variation in the future potential labour supply in different countries embedding different labour market systems. The paper, first introduces a new concept of Labour Potential. Second, projections for the level of Labour Potential in the Nordic regions are presented up to 2021. The results reveal large variations in the future levels of Labour Potential in the Nordic regions not necessarily revealed by the variation in ageing patterns.
Keywords: R11; R23; J11; J21; J26; 330; Potential labour supply; regional forecasting; ageing; Granger analysis